Effect of itraconazole on the quality of life in patients with moderate to severe seborrheic dermatitis: a randomized, placebo-controlled trial - Zaheer Abbas (Mattioli1885, 2016)
Background: Few studies have examined the effect of seborrheic dermatitis (SD) and/or its consequent therapy on a patient’s quality of life. Itraconazole has been suggested as an effective therapy for severe SD but its impact on Quality of Life (QoL) in these patients has never been studied before.